Cognitive biology : evolutionary and developmental perspectives on mind, brain, and behavior - Tommasi, Luca, 1970-; Peterson, Mary A., 1950-; Nadel, Lynn (Vienna series in theoretical biology., 2009)
This text is an overview of current research at the intersection of psychology and biology which integrates evolutionary and developmental data and explanations.